Impacts of ocean-atmosphere teleconnection patterns on the south-central United States - Rohli, Robert V.; Snedden, Gregg A.; Martin, Elinor R.; DeLong, Kristine L. (Frontiers in Earth Science, 2022)
Recent research has linked the climate variability associated with ocean-atmosphere teleconnections to impacts rippling throughout environmental, economic, and social systems. This research reviews recent literature through 2021 in which we identify linkages among the major modes of climate variability, in the form of ocean-atmosphere teleconnections, and the temperature and precipitation of the South-Central United States (SCUSA), consisting of Arkansas, Louisiana, New Mexico, Oklahoma, and Texas. The SCUSA is an important areal focus for this analysis because it straddles the ecotone between humid and arid climates in the U.S.A. and has a growing population, diverse ecosystems, robust agricultural and other economic sectors including the potential for substantial wind and solar energy generation. Whereas a need exists to understand atmospheric variability due to the cascading impacts through ecological and social systems, our understanding is complicated by the positioning of the SCUSA between subtropical and extratropical circulation features and the influence of the Pacific and Atlantic Oceans, and the adjacent Gulf of Mexico. The Southern Oscillation (SO), Pacific-North American (PNA) pattern, North Atlantic Oscillation (NAO) and the related Arctic Oscillation (AO), Atlantic Multidecadal Oscillation/Atlantic Multidecadal Variability (AMO/AMV), and Pacific Decadal Oscillation/Pacific Decadal Variability (PDO/PDV) have been shown to be important modulators of temperature, and precipitation variables at the monthly, seasonal, and interannual scales, and the intraseasonal Madden-Julian Oscillation (MJO) in the SCUSA. By reviewing these teleconnection impacts in the region alongside updated seasonal correlation maps, this research provides more accessible and comparable results for interdisciplinary use on climate impacts beyond the atmospheric-environmental sciences.